Probability and algorithms - Council, National Research; Sciences, Division on Engineering and Physical; Commission on Physical Sciences, Mathematics, and Applications; Algorithms, Panel on Probability and (National Academy Press, 1992)
Some of the hardest computational problems have been successfully attacked through the use of probabilistic algorithms, which have an element of randomness to them. Concepts from the field of probability are also increasingly useful in analyzing the performance of algorithms, broadening our understanding beyond that provided by the worst-case or average-case analyses.This book surveys both of these emerging areas on the interface of the mathematical sciences and computer science. It is designed to attract new researchers to this area and provide them with enough background to begin explorations of their own.